2018
DOI: 10.1016/j.eats.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Precut Osteochondral Allograft Core Transplantation for the Treatment of Femoral Cartilage Defects

Abstract: Fresh osteochondral allograft (OCA) transplantation is a successful single-stage procedure for the treatment of symptomatic cartilage defects of the knee. Although long-term studies reveal reliable improvements in patient-reported outcome scores and graft survival, the limitations of the procedure include graft availability and timely use prior to expiration. To avoid prolonged surgical wait times and progression of lesion size, some surgeons have employed the use of nonorthotopic grafts (e.g., lateral femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Fresh precut allograft cores offer an advantage with regards to expediency of surgery. 26 Prolonged wait times for surgery are a concern particularly in the young, active population, in whom the literature has shown that continued weight-bearing on the lesion can cause possible progression in size and severity. 27,28 Recent studies have demonstrated that nonorthotopic grafts can still achieve excellent surface matches at the recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh precut allograft cores offer an advantage with regards to expediency of surgery. 26 Prolonged wait times for surgery are a concern particularly in the young, active population, in whom the literature has shown that continued weight-bearing on the lesion can cause possible progression in size and severity. 27,28 Recent studies have demonstrated that nonorthotopic grafts can still achieve excellent surface matches at the recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…If the needed plug size is in between those that are commercially available a smaller diameter plug may be harvested from a larger diameter plug using a commercially available single-use OAT harvester. 129
Figure 6. Osteochondral allograft transplantation (OCA). ( A ) Osteochondral lesion in the lateral femoral condyle.
…”
Section: Overview Of Cartilage Restoration Techniquesmentioning
confidence: 99%
“…If the needed plug size is in between those that are commercially available a smaller diameter plug may be harvested from a larger diameter plug using a commercially available single-use OAT harvester. 129…”
Section: Overview Of Cartilage Restoration Techniquesmentioning
confidence: 99%
“…If plugs smaller than 10 mm in diameter are required, the same size disposable single-use OAT harvester used for the donor graft(s) can be used to downsize the plugs according to the technique previously described by the senior author. 8 A metal sizing tamp is placed in each donor site, and the arthroscope is used to confirm the depth of the donor site at the 3-, 6-, 9-, and 12-o'clock positions ( Fig 6 , A and B). A skin marker and metal ruler or sizing tamp are then used to mark the appropriate lengths at the 12-, 9-, 6-, and 3-o'clock positions ( Fig 7 , A and B).…”
Section: Surgical Technique (With Video Illustration)mentioning
confidence: 99%